LEARNER AUTONOMY IN THE LIGHT OF FREIRE - NICOLAIDE, Christine Siqueira; FERNANDES, Vera (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2016)
Concepts on autonomy in language learning usually converge to the responsibility over one’s own learning. This paper aims to emphasize that learner autonomy is also a matter of getting involved with the social environment in which the learner is inserted in. This conception will be analyzed in the light of Freire’s Critical Pedagogy. OTÁVIO, considered a ”rebel” by his own teachers, is brought up as a case study to illustrate kinds of transformation, which might happen under the influence of the environment and of the opportunities generated in it.